penerapan - Iqbal, Muhammad; Subhan, Muhammad (Gravity Edu : Jurnal Pembelajaran dan Pengajaran Fisika, 2023)
Solar Dryer-based Greenhouse or also known as the drying method using the Greenhouse Effect (ERK) is a drying method that utilizes solar energy as the main energy source. The aim of this research is to produce a Greenhouse Prototype and determine the effectiveness of the Solar Dryer-based Green House Prototype that was developed and the coffee bean comparison aims to get a comparison of the blending of Arabica and Robusta coffee beans. The results of the research show that the effect of drying time on the room temperature distribution of the drying house looks slightly fluctuating. However, the average room temperature from several measurement points is relatively uniform with a higher value than the environment. The moisture content value on a wet basis is 3.17%, on a dry basis 3.07% and the average final moisture content of coffee beans is 20.45%, the drying rate is 0.77% bw/hour, and the efficiency of the drying house is 4.84%. Meanwhile, for blending coffee beans based on consideration of organoleptic test results, yield, water content, VRS, shelf life. The initial quality characteristics of the selected ground coffee meet SNI standards with water content values ​​of 3.54%, fat content 4.77%, fiber content 58.63%, protein content. 12.92%, and ash content 5.76%. During storage of selected ground coffee, there was a decrease in quality, which was characterized by an increase in water content, a decrease in VRS levels, and an increase in pH value.